COMPARATIVE STUDY OF STRUCTURAL-SEMANTIC ASPECTS OF HYPOTAXEMAS WITH CONDITIONAL COMPONENTS IN ENGLISH AND UZBEKI (Scientific journal of the Fergana State University, 2024)
The article is devoted to the comparative analysis of hypotaxemes with a conditional component and their structural-semantic types in English and Uzbek languages, in which the similar and different aspects of them in both languages are studied, and the factors that require them are revealed.